Identificação e caracterização de alvos para controle do inseto Diaphorina citri, vetor da doença do citros Huanglongbing - Ferrara, Taise Fernanda da Silva [UNIFESP] (2018)
Huanglongbing (HLB or citrus greening) is a bacterial disease that affects the citrus crop and nowadays represent the greatest threat to the world's citrus industry. HLB is associated with the phloemlimited bacterium Candidatus Liberibacter asiaticus (CLas) that is transmitted by the vector insect Diaphorina citri. D. citri psyllid belongs to the hemiptera order and has in its digestive tract enzymes of the class of cysteine peptidases as the most abundant proteolytic enzymes, being able to be involved in different processes of development in the insect. In this context, the aim of this work was the identification, cloning, recombinant expression, enzymatic characterization and gene expression analysis of two cysteine peptidases such as cathepsin Blike (DCcatB2) and a cathepsin Llike (DCcatL1) of insect D. citri. The recombinant proteins expressed in Rosetta E. coli cells (DE3) were solubilized in ureacontaining buffer, purified by affinity chromatography and renatured by the refolding process. The enzyme DCcatL1 was activated at pH 4.5 and presented higher activity at 37°C. The catalytic activity was determined using the fluorogenic substrates ZFRAMC and ZLRAMC. DCcatL1 presented higher affinity by ZFRAMC with a Km of 12.29 μM and a kcat/Km = 63 M1s1 and was efficiently inhibited by E64 and by four citrus recombinant cystatins (CclemCPI1, CclemCPI2, CsinCPI1 and CsinCPI2). The cystatin CsinCPI2 showed higher inhibitory potency against DCcatL1 with a Ki = 4.46 pM. The analysis of DCcatL1 gene expression showed high expression in the gut of D. citri, being 2.59 times higher than in head and 2.87 times than in carcass. In the developmental phases, DCcatL1 was more expressed in egg, than in nymph and adult, suggesting a nondigestive and therefore a lysosomal role for this enzyme. The enzyme DCcatB2 was activated at pH 4.0 exhibiting higher affinity for the ZFRAMC substrate (Km = 42.97 μM) when compared to ZRRAMC (Km = 78.9 μM). The activity of DCcatB2 was strongly inhibited by the cathepsin B specific inhibitor CA074 and by the cystatin CclemCPI1 with a Ki of 12 nM and 7.6 nM, respectively. The analysis of the gene expression of DCcatB2 in the developmental phases of D. citri showed a high expression in egg, when compared to nymph and adult. In the body parts of D. citri, DCcatB2 was 6.8 times more expressed in carcass and 5.2 times in head when compared to the gut, suggesting a nondigestive and non lysosomal role for this enzyme. Our results point DCcatL1 and DCcatB2 as promising targets for the development of a control strategy against HLB.